ENTREPRENEUSHIP TRAINING NEED ANALYSIS AMONG URBAN LOW INCOME TEENAGERS - Siti Fardaniah Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2018)
Teenagers living in the area of citizen housing project (PPR) Kuala Lumpur iscategorized as urban low income teenagers; in which, their family average income is less thanRM940 per month. Previous studies have shown that this community is experiencing economicpressures that plunge them into other problems such as social, crime, drug and fights.Volume: 3 Issue: 11 [June, 2018] pp. 96 - 105]Journal of Islamic, Social, Economics and DevelopmenteISSN: 0128-1755Journal website: www.jised.comm97Therefore, the community needs to be helped so that they are not in constant economic pressure.One of the efforts that can be done to assist the community is to provide human developmentprograms; for example, Entrepreneurial Skills Programs so that they can choose to beentrepreneur and thus increase their household income. Hence, a training need analysis wasconducted to determine the level of knowledge, skills and entrepreneurship interests among 92teenagers at PPR Pantai Dalam and Desa Rejang, Kuala Lumpur. Findings show that only41.3% of these teenagers passed an informal quiz on entrepreneurial knowledge. In addition,based on self-perception, majority of them perceived that the level of knowledge, skills andinterest in entrepreneurship was only at a moderate level. This suggests that there is a need toincrease their level of knowledge, skills, and interests in the field of entrepreneurship throughappropriate training program.